Membangun Pengalaman Belajar Kewarganegaraan melalui Model Pembelajaran Project citizen pada Siswa - Surya Dharma; Rosnah Siregar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2015)
Education indeed could be takes place through experiences which empirically can develops culture of learning for every students. However experience and education can not merely be equated because part of experience could not be educate. The not-educated experience is the one that obstruct on coming of the next experience. Whilst educated learning experience is the one that can encourage the students to evolve a change intentionally, so the change could be happen actively, effectively, and sustainable. This wiriting tries to construct, how the learning model of poject citizen can be develop experience in learning concern on civic. If realized that one of the matters in teaching civic nowadays is managing of class can not yet construct an atmosphere that can be provides experiences in learning for students, as the learning only emphasizes on cognitive aspect. Through community services activity, a training by using learning model  of ‘project citizen’ have done in SMP of Batubara Regency, the writer try various ideas regarding how learning model of project citizen could be constructs experience in learning civic .